WALI ADHOL KARENA FAKTOR ADAT DITINJAU MENURUT HUKUM ISLAM (STUDI PUTUSAN PENGADILAN AGAMA BENGKALIS NOMOR: 41/PDT.P/2013/PA.BKLS) - Khoiri; Rismawati (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Abstract Adhol guardians are guardians who do not want to marry someone, adhol guardians are permitted as long as they do not conflict with Islamic law. Interesting to examine here is the decision of the Bengkalis Religious Court Number: 41/Pdt.P/2013/PA.Bkls, which can be identified in the Bengkalis Religious Court accepting, adjudicating and determining the walii adhol case due to customary factors, even though the two candidates have already established a relationship. It's been a long time and it's hard to separate, it's been 2 years and they love each other. The future husband has a very suitable salary to build a household to meet his household needs, and the prospective husband has approached his future wife's biological father as much as possible to be willing to accept the proposal from the prospective wife. her husband, but her biological father still refused on the grounds of customary issues. The results of research on the basis of judges' considerations in deciding or determining cases refer to Article 23 paragraph (2) of Legislation No. 1 of 1991 concerning the Compilation of Islamic Law which basically states that among the absolute competencies of the Religious Courts is to receive, examine and determine cases at the court of first instance, PA Bengkalis has direct authority to adjudicate these cases, so that in formal and material procedural law, in cases has fulfilled the requirements, the panel of judges is obliged to analyze and decide the walii adhol case. The panel of judges determines or decides cases in accordance with the rules of fiqh regarding the obligations of leaders or judges towards the community in terms of decisions or policies to determine a case in the Religious Court. So if the panel of judges does not determine the adhol guardian, things that are prohibited by the Shari'ah will happen. Keywords: Wali Adhol, PA. Bengkalis No. 41/Pdt.P/2013/PA.Bkls, Islamic Law